Pengaruh Pemberian Tepung Tempe terhadap Kadar Kolesterol Total Darah Mencit (Mus musculus) Hiperkolesterol - Rumtal, Heryl; Ngitung, Rosdiana; A. Mu’nisa, A. Mu’nisa (bionature, 2019)
Abstract. This research is experimental which aims to determine the effect of giving Tempe Flour to total blood cholesterol concentration of hypercholesterol mice (Mus musculus). The independent variable of this research Tempe Flour while the dependent variable is the total blood cholesterol concentration of mice (Mus musculus). The subject of this research is 25 male ICR strain (Imprinting Control Region) mice with 3 months age divided 5 treatment groups which are normal group, hypercholesterol group, giving of tempe flour at dose of 10 g / day / BB (P1), 20 g / days / BB (P2) and 25 g / day / BB (P3). Tempe flour is given after the giving of cholesterol feed. All mices blood cholesterol concentration were check after the time of treatment. The result is analyz by using ANOVA with Ducan test. The result of this research show that the giving of Tempe Flour affected the decrease of blood cholesterol concentration of mice (Mus musculus) in dose of 10 g/day/BB,20 g/day/BB and 25 g/day/BB. Dose of 25 g/day/BB showed an effective dose for lowering cholesterol in the research.   Keywords: tempe flour, cholesterol, hypercholesterol, mencit (Mus musculus)